2022-RA-765-ESGO The impact of delay from diagnosis to surgery in early ovarian cancer. (20th October 2022) - Tsolakidis, Dimitrios; Zouzoulas, Dimitrios; Theodoulidis, Vasilis; Chatzistamatiou, Kimon; Anthoulakis, Christos; Pitis, Sotiris; Karalis, Tilemaxos; Aristotelidis, Michalis; Zioga, Eva; Mpili, Eleni; Pados, George; Grimbizis, Grigoris
Abstract : Introduction/Background: In the COVID-19 era, surgery waiting list is longer and gynecological-oncological units are forced to delay oncological surgery, especially suspected early-stage cancers, like ovarian cancer (OC). The aim of this study is to evaluate the impact of delay on the oncological outcomes of these patients. Methodology: Retrospective analysis of all women with early OC treated in the 1st Department of Obstetrics & Gynecology AUTh at 'Papageorgiou' Hospital, from 2012 – 2019. Delay was calculated as the time interval between the day of first examination in the outpatient clinic and the day of surgery, and a cut-off point at 6 weeks was set. Patient and tumor characteristics, treatment options and follow-up information were collected. Primary outcomes were postoperative complication and survival rates. Results: 72 patients met the inclusion criteria. Based on the 6-week cutoff point, patients were divided into two groups: 38 underwent surgery up to 6-weeks (group A) and 34 over 6-weeks (group B). There was no statistical difference in the age, BMI or comorbidities between the two group, but patients in group A had higher pre-operative CA125 level and patients in group B had a significantly higher blood loss during surgery (300 vs. 200cc, p=0.0348). However, no difference was detected in the post-operative complications rate (Clavien – Dindo Classification), hospital stay, ICU admittance and surgery duration. Concerning survival rates, there was no statistical difference in disease-free (p=0.792) and overall survival (p=0.507). Conclusion: Delaying surgery for suspected early OC over 6 weeks seems to be relatively safe, with no impact on the mortality, morbidity and recurrence rate of these patients. However, it is very important to careful evaluate our OC patients in the pre-operative setting with all available imaging modalities [CT, MRI, Ultrasound (IOTA Score)].